Biomechanical Analysis of Movement and Knee Injury Risk in Football Athletes Using Three-Dimensional Motion Capture System - Hasyim Hasyim; Muslim Bin Ilyas (SHOOTING: Journal of Sport, Health, and Education, 2026)
Knee injuries represent one of the most prevalent and debilitating musculoskeletal conditions affecting football athletes worldwide. This study aimed to analyze the biomechanics of lower extremity movement and quantify knee injury risk in football athletes using a three-dimensional (3D) motion capture system. A total of 30 male football athletes from the Faculty of Sports and Health Sciences, Universitas Negeri Makassar, were recruited as participants (mean age: 20.4 ± 1.8 years; mean height: 170.2 ± 4.6 cm; mean body mass: 65.3 ± 5.2 kg). Kinematic and kinetic data were collected during standardized football-specific tasks including running, cutting maneuver, and single-leg landing using the Vicon motion capture system (10 cameras, 200 Hz) integrated with force plates. Key biomechanical parameters including knee valgus angle, knee flexion angle, ground reaction force, and valgus knee moment were analyzed. Results demonstrated that during cutting maneuvers, athletes exhibited peak knee valgus angles of 12.7 ± 3.4° and peak knee flexion angles of 42.3 ± 6.8°. Ground reaction forces reached 2.8 ± 0.4 times body weight during single-leg landing tasks. Knee abduction moment values averaged 0.34 ± 0.09 Nm/kg during cutting tasks, a value associated with elevated anterior cruciate ligament (ACL) injury risk. Significant correlations were found between knee valgus angle and knee abduction moment (r = 0.78, p < 0.001). These findings provide important baseline biomechanical data for developing targeted injury prevention programs for football athletes in the Indonesian context and underscore the clinical utility of 3D motion capture technology in sports science research. (Cedera lutut merupakan salah satu kondisi muskuloskeletal yang paling umum pada atlet sepak bola. Studi ini menganalisis biomekanika gerak ekstremitas bawah dan risiko cedera lutut menggunakan sistem motion capture 3D